The sustainability of groundwater in semi-arid regions: The case of Makutupora basin in Tanzania - Mseli, Zaina Hussein; Said, Alfred; Sankaranna, Gaduputi; Mwegoha, William J. S. (IWA publishing, 2024)
A research paper submitted to AQUA water infrastructure, ecosystems and society Volume 72, Issue 9, 1 September 2023